Venomous Snakes and Envenomation in Brunei - Das, Indraneil; Charles, J.K (Springer Netherlands, 2015)
The venomous snakes recorded from Brunei Darussalam are enumerated. A total of 19 species, representing two families (Elapidae, 15 species, and Viperidae, four species), have been recorded in the country. For each species, there is a brief description of biology, localities, and references. Antivenom sera available at RIPAS Hospital are listed and annotated with their potential use. Apart from bites from venomous snakes, the presence of one “spitter,” the equatorial cobra, Naja sumatrana, increases the risk of humans to venom ophthalmia. Finally, future directions for research and management of snake envenomation, and for enhancing knowledge of the country’s snakes for conservation and improving health care, are discussed.